Fly like a fly [micro-air vehicle]. - Zbikowski, R.
A team of scientists has built a fly-size flight simulator in an attempt to understand flight control from the perspective of the common housefly. Results so far have shown, and further tests are expected to confirm, that the fly uses a flight control paradigm that is completely different from that of a fighter jet. Whereas the F-35 Joint Strike Fighter takes a few measurements and then plugs them into complex equations, which it must solve in real time, the fly relies on many measurements from a variety of sensors but does relatively little computation. By discovering the fly's flight control scheme, the scientists hope to derive important lessons for the design of micro air vehicles, which attempt to approximate insect flight, and for high-performance aircraft in general.
Keywords: F-35 Joint Strike Fighter; Air vehicles; Aircraft; Fighter jet; Flight control; Fly-size flight simulator; Housefly; Insect flight; Sensors